DNA storage in thermoresponsive microcapsules for repeated random multiplexed data access - Bögels, Bas W. A.; Nguyen, Bichlien; Ward, David; Gascoigne, Levena; Schrijver, David P.; Pistikou, Anna-Maria Makri; Joesaar, Alex; Yang, Shuo; Voets, Ilja K.; Mulder, Willem J. M.; Phillips, Andrew; Mann, Stephen; et al. (Nature Nanotechnology, 2023)
DNA has emerged as an attractive medium for archival data storage due to its durability and high information density. Scalable parallel random access to information is a desirable property of any storage system. For DNA-based storage systems, however, this still needs to be robustly established. Here we report on a thermoconfined polymerase chain reaction, which enables multiplexed, repeated random access to compartmentalized DNA files. The strategy is based on localizing biotin-functionalized oligonucleotides inside thermoresponsive, semipermeable microcapsules. At low temperatures, microcapsules are permeable to enzymes, primers and amplified products, whereas at high temperatures, membrane collapse prevents molecular crosstalk during amplification. Our data show that the platform outperforms non-compartmentalized DNA storage compared with repeated random access and reduces amplification bias tenfold during multiplex polymerase chain reaction. Using fluorescent sorting, we also demonstrate sample pooling and data retrieval by microcapsule barcoding. Therefore, the thermoresponsive microcapsule technology offers a scalable, sequence-agnostic approach for repeated random access to archival DNA files.